2021
DOI: 10.1186/s11671-021-03547-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multi-concentration Cu:Ag Bimetallic Nanoparticles as a Promising Bactericidal for Antibiotic-Resistant Bacteria as Evaluated with Molecular Docking Study

Abstract: The present study is concerned with evaluating the influence of various concentrations of Ag within Cu:Ag bimetallic nanoparticles developed for use as a promising anti-bacterial agent against antibiotic-resistant bacteria. Here, Cu:Ag bimetallic nanoparticles with various concentration ratios (2.5, 5.0, 7.5, and 10 wt%) of Ag in fixed amount of Cu labeled as 1:0.025, 1:0.050, 1:0.075, and 1:0.1 were synthesized using co-precipitation method with ammonium hydroxide and deionized water as solvent, polyvinyl pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…They were non-toxic and TMNPs were the safest, as demonstrated in Table 2. The anti-cancer properties of Au, Ag, and CuO NPS as monometallic or bimetallic NPs were reported by many investigators such as Zhou et al and Hossen et al [16,45]. TMNPs have high catalytic activity compared to their bimetallic or monometallic nanoparticles [46].…”
Section: Anti-cancer Activitymentioning
confidence: 88%
“…They were non-toxic and TMNPs were the safest, as demonstrated in Table 2. The anti-cancer properties of Au, Ag, and CuO NPS as monometallic or bimetallic NPs were reported by many investigators such as Zhou et al and Hossen et al [16,45]. TMNPs have high catalytic activity compared to their bimetallic or monometallic nanoparticles [46].…”
Section: Anti-cancer Activitymentioning
confidence: 88%
“…The obtained results were in accordance with many recent studies conducted in 2021 on the antimicrobial activities of different nanoparticles either alone or in combination with other antimicrobials have proved activity against various pathogens. These included, Casein-silver NPs combined with TGC against A. baumannii , 72 antibiofilm and anti-virulence potential of silver NPs against MDR A. baumannii , 73 Cu:Ag bimetallic NPs for antibiotic-resistant bacteria, 74 Lignin-Capped silver NPs, 75 Smaller Copper Oxide Nanoparticles against MDR Bacteria, 76 colistin-integrated chitosan nanoparticles. 77 Our results revealed that CNPs when combined with MEM significantly increased the susceptibilities of the MDR A. baumannii isolates by 100% as compared to MEM alone.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophilic functional groups capped on the surface of N, S-CQDs are responsible for their water solubility. 52,53 FT-IR analysis of N, S-CQDs surface show different functional groups [54][55][56][57] as illustrated in Fig. 4.…”
Section: Synthesis and Characterization Of Uorescent Probementioning
confidence: 99%